The influence of hormone therapy on the sexual life of women at menopausal age - Bakalczuk, Grzegorz; Bakalczuk, Szymon (Menopause Review/Przegląd Menopauzalny, 2009)
A complex approach to women’s sexuality becomes especially difficult during menopause. Oestrogen insufficiency causes anatomical and psychological changes. Menopausal symptoms which have an influence on women’s sexual life should be treated by hormone replacement therapy with androgen drugs (tibolone). The influence of testosterone and DHEA on women’s sexual life should be further investigated.